Is There Any Relation Between the Position of Cycling and the Appearance of Lower Pain? a Systematized Review [¿Existe Alguna Relación Entre la Posición del Ciclismo y la Aparición de Dolor Lumbar? Una Revisión Sistematizada] - Martinez-Salinas, J; Arriagada-Tarifeno, D (Federacion Espanola de Docentes de Educacion Fisica, 2021)
This article analyzed the relationship between the flexion position maintained during cycling and the possible relationship with low back pain. A systematic review was carried out through the PRISMA process between 2015-2020, in the PubMed, PEDro, Scopus and Web of Science databases, using the terms; «cycling», «cyclist», «position», «positioning», «injury from overuse», «biomechanics of the spine», «lumbar region», «low back pain». Five articles were selected that met all the inclusion criteria. Selected articles showed changes in pelvic tilt, torso flexion angles in medium and low strokes of the handlebars of the road bike and mountain bike, variations of the highest seat or the appropriate backrest according to the groin length, knee position 40 and trunk 35° simultaneously when the pedal is at 180°, while in anatomical position they have been described; The maximum angle of pelvic tilt in anteversion, the maximum angle of pelvic tilt in retroversion and the maximum angle of lumbar flexion are associated with pain or discomfort in the lumbar region. However, it is possible to establish that the association between cycling and low back pain has not been sufficiently studied, which leads us to infer that there is a need to update the information in order to prevent this type of injury associated with the position in cycling. © 2021 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.